Relevansi Teori Kognitif Menurut Jerome Seymour Bruner terhadap Strategi Pembelajaran Bermakna di Era Digital - Surur, Misbahul; Alifudin, Muhamad; muminin, Nashrul; Syafitri, Lely Hidayah Nur (Universitas Cokroaminoto Yogyakarta, 2023)
This study examines the relevance of Jerome Bruner's cognitive theory to meaningful learning in the digital age. Using a literature review method, it was found that Bruner's discovery learning concept, three modes of representation, and spiral curriculum remain effective when combined with technologies such as LMS and AR/VR. The study results indicate that the integration of Bruner's theory and technology can increase cognitive engagement and create active and contextual learning.